Answer:
840mi. - 12 hrs
x - 3 hrs
This is a simple cross multiplying problem.
840 _ 12
x -- 3 ⇒12x=3(840) ⇒ 4x=280 ⇒ x=70 miles
:D
Step-by-step explanation:
Answer:
![y=2x^2-\frac{4}{3}x-\frac{10}{3}](https://tex.z-dn.net/?f=y%3D2x%5E2-%5Cfrac%7B4%7D%7B3%7Dx-%5Cfrac%7B10%7D%7B3%7D)
Step-by-step explanation:
we know that
The roots of the quadratic function (x-intercepts) are
x=-1 and x=5/3
so
we can write the equation of the parabola as
![y=a(x+1)(x-\frac{5}{3})](https://tex.z-dn.net/?f=y%3Da%28x%2B1%29%28x-%5Cfrac%7B5%7D%7B3%7D%29)
where
a is a coefficient
Remember that
The parabola pass through the point (5,40)
substitute the value of x and the value of y of the ordered pair in the quadratic equation and solve for a
x=5, y=40
![40=a(5+1)(5-\frac{5}{3})](https://tex.z-dn.net/?f=40%3Da%285%2B1%29%285-%5Cfrac%7B5%7D%7B3%7D%29)
![40=a(6)(\frac{10}{3})](https://tex.z-dn.net/?f=40%3Da%286%29%28%5Cfrac%7B10%7D%7B3%7D%29)
![40=20a\\a=2](https://tex.z-dn.net/?f=40%3D20a%5C%5Ca%3D2)
substitute
![y=2(x+1)(x-\frac{5}{3})](https://tex.z-dn.net/?f=y%3D2%28x%2B1%29%28x-%5Cfrac%7B5%7D%7B3%7D%29)
apply distributive property
![y=2(x^2-\frac{5}{3}x+x-\frac{5}{3})\\\\y=2(x^2-\frac{2}{3}x-\frac{5}{3})\\\\y=2x^2-\frac{4}{3}x-\frac{10}{3}](https://tex.z-dn.net/?f=y%3D2%28x%5E2-%5Cfrac%7B5%7D%7B3%7Dx%2Bx-%5Cfrac%7B5%7D%7B3%7D%29%5C%5C%5C%5Cy%3D2%28x%5E2-%5Cfrac%7B2%7D%7B3%7Dx-%5Cfrac%7B5%7D%7B3%7D%29%5C%5C%5C%5Cy%3D2x%5E2-%5Cfrac%7B4%7D%7B3%7Dx-%5Cfrac%7B10%7D%7B3%7D)
see the attached figure to better understand the problem
Answer:
N = -7
Step-by-step explanation:
4 = 1 - n -4
Subtract the numbers first
1 - 4 = -3
Then rearrange the terms
4 = -3 - n
-----> 4 = n - -3
The you add 3 to both sides of the equations
4 + 3 = -n - 3 + 3
![\bf \begin{cases} f(x)=\sqrt[3]{7x-2}\\\\ g(x)=\cfrac{x^3+2}{7} \end{cases}\\\\ -----------------------------\\\\ now \\\\ f[\ g(x)\ ]\implies f\left[ \frac{x^3+2}{7} \right]\implies \sqrt[3]{7\left[ \frac{x^3+2}{7} \right]-2}\implies \sqrt[3]{x^3+2-2} \\\\\\ \sqrt[3]{x^3}\implies x\\\\ -----------------------------\\\\ or \\\\ g[\ f(x)\ ]\implies g\left[\sqrt[3]{7x-2}\right]\implies \cfrac{\left[\sqrt[3]{7x-2}\right]^3+2}{7} \\\\\\ \cfrac{7x-2+2}{7}\implies \cfrac{7x}{7}\implies x](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Bcases%7D%0Af%28x%29%3D%5Csqrt%5B3%5D%7B7x-2%7D%5C%5C%5C%5C%0Ag%28x%29%3D%5Ccfrac%7Bx%5E3%2B2%7D%7B7%7D%0A%5Cend%7Bcases%7D%5C%5C%5C%5C%0A-----------------------------%5C%5C%5C%5C%0Anow%0A%5C%5C%5C%5C%0Af%5B%5C%20g%28x%29%5C%20%5D%5Cimplies%20f%5Cleft%5B%20%5Cfrac%7Bx%5E3%2B2%7D%7B7%7D%20%5Cright%5D%5Cimplies%20%5Csqrt%5B3%5D%7B7%5Cleft%5B%20%5Cfrac%7Bx%5E3%2B2%7D%7B7%7D%20%5Cright%5D-2%7D%5Cimplies%20%5Csqrt%5B3%5D%7Bx%5E3%2B2-2%7D%0A%5C%5C%5C%5C%5C%5C%0A%5Csqrt%5B3%5D%7Bx%5E3%7D%5Cimplies%20x%5C%5C%5C%5C%0A-----------------------------%5C%5C%5C%5C%0Aor%0A%5C%5C%5C%5C%0Ag%5B%5C%20f%28x%29%5C%20%5D%5Cimplies%20g%5Cleft%5B%5Csqrt%5B3%5D%7B7x-2%7D%5Cright%5D%5Cimplies%20%5Ccfrac%7B%5Cleft%5B%5Csqrt%5B3%5D%7B7x-2%7D%5Cright%5D%5E3%2B2%7D%7B7%7D%0A%5C%5C%5C%5C%5C%5C%0A%5Ccfrac%7B7x-2%2B2%7D%7B7%7D%5Cimplies%20%5Ccfrac%7B7x%7D%7B7%7D%5Cimplies%20x)
thus f[ g(x) ] = x indeed, or g[ f(x) ] =x, thus they're indeed inverse of each other